La interculturalidad como cohesión del turismo sostenible en el Resguardo Ticoya, Amazonas (2021)
This article focuses on the possible interdependence between interculturality and the so-called sustainable tourism, and how it is applied in a real scenario, in this case, the community of the Ticoya reserve, in the Department of Amazonas. Therefore, through a case study, the analysis focuses specifically on the territory comprising the Ticoya Reserve, in the Municipality of Puerto Nariño, located in the cross-border area between Peru, Brazil and Colombia, between the Amazon, Atacuari, Boyahuasú, Loretoyacu and Amacayacu rivers. There is a great natural wealth of the territory and, especially, the interculturality of bringing together three ethnic groups: Ticunas, Cocamas and Yaguas, which, from their cultural practices, have sought to build and consolidate spaces for dialogue, reflection and analysis for the conservation and protection of their territories. In this context, this article is the product of a research exercise that has been developed with the community of the Ticoya Reserve since 2016 and aims to reflect on how the intercultural diversity in the Reserve (a result of the diversity of the three ethnic groups that comprise it and reflected in the richness of its gastronomy, language, architecture, crafts, music, among other things) could become an articulator for the development of sustainable tourism activities, which ensure the protection of their territory and the conservation of their culture. Regarding the methodology, the sources of the research are qualitative and are based on the analysis of documents such as the Life Plan of the Reserve and the Municipal Development Plan. In addition, from the results obtained from a participant observation exercise, in this case carried out through a collaborative training process with representatives of the 22 communities of the reserve in 2019.